Web service workflow selection using system and network QoS constraints. (28th December 2007) - Panagis, Yannis; Papakonstantinou, Konstantinos; Sakkopoulos, Evangelos; Tsakalidis, Athanasios
Web services serve as a leading technology platform for web-based data-centric environments providing flexibility of loose coupling, message-based communication. Interest in more efficient web services selection strategies is rather requisite especially from the business process workflow perspective. We present several strategies to efficiently select a set of web services performing a workflow, fulfilling quality specifications at all workflow steps. The focus is on finding the best performing web service given a history of the execution times and current measured variation in operating system and network resource consumption. To assess their efficiency, we experimentally evaluate them and present comparative results, which strongly indicate that they can effectively reduce the overall workflow execution time in a web service-based workflow with QoS constraints. Approaches are presented for a number of workflows depending on their particular characteristics.